Propuesta de un modelo de gestión por competencias orientado al personal administrativo de la Universidad Politécnica Salesiana, Sede Cuenca para el año 2014 - Mena Juna, Wilma Anita (2014)
This Postgraduation project,“ The Proposal of Competency Management Model, oriented to the Administrative staff of the Politecnica Salesiana University, in Cuenca, for 2014, “ is developed in four chapters: the first one is an bibliographic study about quality, Competency Management, management, Human Resources development, assessment and the continuous improvement based on the Competency Management. The second chapter is an overview of how the Politecnica Salesiana University is presented through a historical summary; additionally, with its Vision, Mission, Institutional policies, Organization structure, Academic offer, and Administrative staff status. The identification of the Administrative Institution staff competencies is done through a diagnostic test, which results are presented in chapter three. The final part, found in the fourth chapter, determines the training areas, and defines a formative proposal for continuous improvement, based on the Competency Management model.